Perancangan Kursi Roda Naik Tangga Pada Stasiun Sebagai Alat Bantu Orang Berkebutuhan Khusus - Winjaya, Fathurrozi; Darmawan, Arief (Politeknik Perkeretaapian Indonesia Madiun, 2020)
Intelligent wheelchairs are motorized resting media designed to help users with physical limitations, where an artificial control system is added or used to replace user controls. The aim is to reduce or eliminate the user's duty to drive a motorized wheelchair. At the station there are still many places that are still not accessible by persons with disabilities. As the difference between platform and train height, usually there are stairs that support to enter the train. Therefore the writer makes an innovation so that it can make it easier for people with disabilities to move up stairs in a wheelchair. The design of the wheelchair design uses a crawler type with the help of universal plates from Tamiya, the gearbox uses Twin Motor with a rotation ratio of 204: 1. Servo motor mounted on the seat which is supported by a gyro sensor as a counterweight to the chair when the position of the chair up or down. In the DC motor and servo PID method is added so that the motion changes can be smooth. PID is installed when testing the equilibrium results obtained a little stable oscillation at Kp = 0.27, Ki = 0.0004, and Kd = 0.0001, while when testing the speed obtained the most stable conditions at Kp = 2, Ki = 1, Kd = 0.25.